Valid or not? Yunnan mountain snake Plagiopholis unipostocularis (Serpentes: Colubridae: Pseudoxenodontinae) - Zhong, Guang Hui; Chen, Wen De; Liu, Qin; Zhu, Fei; Peng, Pei Hao; Guo, Peng (Zootaxa, 2015)
Plagiopholis unipostocularis Zhao, Jiang & Huang, 1978 is a small snake endemic to Yunnan, southern China. Its validity is still controversial and unresolved. Based on extensive sampling in Yunnan, we conducted morphological comparison and molecular phylogenetics on the unidentified specimens of Plagiopholis from Yunnan. Based on a combination of morphological comparison and molecular phylogeny, the newly collected specimens could be identified as P. blakewayi. While some specimens exhibit one or more diagnostics of P. unipostocularis, and some characteristics are intermediate between that of Plagiopholis unipostocularis and P. blakewayi. Thus morphological continuities between two species uncovered P. unipostocularis is a synonymy of P. blakewayi, and the diagnostics of this species was revised accordingly.